Features of sound classification scheme designated to label buildings in Lithuania. Issue 3 (3rd April 2017) - Jagniatinskis, Aleksandras; Fiks, Boris; Mickaitis, Marius; Šukys, Ritoldas
Abstract: In Lithuania's case, the legal requirements for the building acoustic quality since the year 2004 has been expressed through the sound classification scheme (SCS). The relationship of the subjective indoor acoustic comfort with the value of objective sound insulation was considered as a core for the classification scheme. SCS was designed to provide at least one sound class as a request for the newly erected building, other lower classes for reconstructed buildings and higher classes for premises with enhanced acoustic comfort. The adopted scheme contains five sound classes with various steps between them and is based on rating by two different sound insulation descriptors both having the same limit value. A request to protect against noise for newly erected and reconstructed buildings was enforced via the mandatory pre-completion acoustical testing. The database collected during testing allowed for the analysis of about 2000 in situ measurements of sound insulation properties of building partitions. It showed that the possibility of selecting either of the two airborne sound insulation descriptors Dn, T, w or R' w ensures better conformity with subjective comfort perception. This paper also addresses the particularities and advantages of simultaneous application of two different descriptors for regulation of sound insulation performance of dwellings.